Al Qur’an dan Upaya Pemanusiaan Penuh Perempuan - Sarwanih, Sarwanih (Journal Of Gender, Child And Humanity Studies, 2024)
This paper aims to analyze the position of women in various major civilizations before the revelation of the Qur'an and the contribution of Islam in changing these perspectives. This research uses the literature review method to explore how women were treated in the pre-Islamic Greek, Roman, Persian, Indian, Chinese, and Jahiliyyah civilizations, and compares them with the Islamic view as stated in the Qur'an. The results show that at that time, women were in a subordinate position and were often seen as property without civil rights. They experienced discrimination in various aspects of life, including social, economic and political. In fact, the religions that developed at that time, such as Judaism and Christianity, often reinforced negative stereotypes against women. In contrast, Islam through the Qur'an brought significant changes by giving equal rights to women. These rights include education, politics, career, social security, leadership, inheritance, and various other aspects, which show high respect for the dignity of women. In conclusion, the Qur'an acts as a revolution in glorifying women, freeing them from the shackles of discrimination, and elevating their status in society. The contribution of this research lies in the finding that such transformation not only impacts women, but also brings about social changes that are more just and inclusive